Effects of drop out in a longitudinal study of musculoskeletal disorders. Issue 3 (1st March 2001) - Bildt, C; Alfredsson, L; Punnett, L; Theobald, H; Torgén, M; Wikman, A
Abstract : OBJECTIVES: The drop out rates in different longitudinal studies of musculoskeletal disorders range between 7% and 57%, and little is known about the characteristics of the subjects who dropped out. The aim was to analyse various consequences of drop out in a longitudinal study of musculoskeletal disorders and occupational risk factors during 1969–97. METHOD: Data about occupational conditions and health in 1969 and in 1993 were analysed. Differences between those who participated throughout (participants) and drop out subjects in these analyses formed the basis for recalculations of earlier reported analyses of associations between occupational conditions and low back pain. In the recalculation the data were weighted to compensate for the differences. RESULTS: More female and male drop out subjects than participants in 1993 had monotonous work, fewer women and more male drop out subjects had heavy lifting in 1969. In 1997, more female and male drop out subjects had had heavy lifting and low stimulation at work in 1993. At both occasions, there were differences between the drop out subjects and participants in occurrence of musculoskeletal disorders. The weighted analyses resulted in changes in risk ratio of 0.1–0.2. CONCLUSIONS: Differences in occupational conditions and health among participants and drop out subjects in a longitudinal study of musculoskeletal disorders and occupational risk factors during 1969–97 did not markedly influence the risk ratios.